2021
DOI: 10.1026/0932-4089/a000369
|View full text |Cite
|
Sign up to set email alerts
|

The Show Must Go On

Abstract: Abstract. By disrupting routines at work, the Covid-19 pandemic may have undermined the extent and effectiveness of health-oriented leadership (HoL) in terms of staff-care and self-care. In a survey with two measurement points in the spring of 2020 ( Nt1=264; Nt2=123), we examined whether the stronger the crisis the lower HoL is, while becoming more effective in terms of follower health. Crisis severity turned out to be indirectly related to exhaustion via staff-care and self-care. Staff-care was more effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Others have since then replicated the scale structure and incremental validity beyond transformational leadership [ 13 , 15 ], in addition to relationships with irritation, psychosomatic complaints, and overall health [ 16 , 35 , 36 , 37 , 38 ]. Self-care and staff care have also been linked to work engagement [ 15 , 17 ], exhaustion and burnout [ 12 , 13 , 15 , 17 , 39 ], physical health [ 13 , 14 ], different indicators of mental health [ 13 , 14 , 29 ], subjective well-being [ 13 ], and performance [ 35 ]. Empirical evidence also supports the notion that self-care and staff care function as resources.…”
Section: Introductionmentioning
confidence: 99%
“…Others have since then replicated the scale structure and incremental validity beyond transformational leadership [ 13 , 15 ], in addition to relationships with irritation, psychosomatic complaints, and overall health [ 16 , 35 , 36 , 37 , 38 ]. Self-care and staff care have also been linked to work engagement [ 15 , 17 ], exhaustion and burnout [ 12 , 13 , 15 , 17 , 39 ], physical health [ 13 , 14 ], different indicators of mental health [ 13 , 14 , 29 ], subjective well-being [ 13 ], and performance [ 35 ]. Empirical evidence also supports the notion that self-care and staff care function as resources.…”
Section: Introductionmentioning
confidence: 99%
“…Since there were effects due to the SARS-CoV-2 pandemic in June 2021, it is questionable to what extent HoL was influenced by this fact. As there is already evidence, that the effectiveness of HoL during crises increases [ 52 ] and by displaying staff-care, leaders can buffer negative effects of crises on followers [ 82 ], it would be interesting to record possible changes in the further course of or after the pandemic as longitudinal data, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…During a health crisis like the COVID-19 pandemic, HRM practices such as training and feedback interventions should focus on leaders' health-related attitudes, values, and behaviors (Rudolph et al, 2019a;Wegge et al, 2014). Indeed, a recent study showed that higher levels of health-oriented leadership mitigated subordinate exhaustion particularly when the COVID-19 pandemic was experienced as crisis; however, results also demonstrated that the more the pandemic was experienced as a crisis, the lower employees' ratings of their supervisors' health-oriented leadership (Klebe et al, 2021).…”
Section: Employee Experiences and Behavior In Times Of Crisis 32mentioning
confidence: 99%